Dysgerminoma with a Somatic Exon 17 KIT Mutation and SHH Pathway Activation in a Girl with Turner Syndrome - Ada Gawrychowska; Ewa Iżycka-Świeszewska; Beata S. Lipska-Ziętkiewicz; Dominika Kuleszo; Joanna Bautembach-Minkowska; Marcin Łosin; Joanna Stefanowicz (Diagnostics, 2020)
This article reports a case of a 7-year-old girl with Turner syndrome, treated with growth hormone (GH), who developed ovarian dysgerminoma. The patient karyotype was mosaic for chromosome Xq deletion: 46,X,del(X)(q22)/45,X. No Y chromosome sequences were present. Molecular studies revealed the presence of a driving mutation in exon 17 of the KIT gene in the neoplastic tissue, as well as Sonic-hedgehog (SHH) pathway activation at the protein level. The patient responded well to chemotherapy and remained in complete remission. This is the first case of dysgerminoma in a Turner syndrome patient with such oncogenic pathway.